Effect of cylinder Orientation on free convective heat transfer in glycerol (Journal of Pure and Applied Sciences (Science Forum), 2025)
The effect of cylinder orientation on the free convective heat transfer inglycerol is studied for the Rayleigh numbers, 10-6 ≤ Ra ≤ 109 and Prandtlnumber, Pr = 11630. While varying the orientation of the cylinder,correlations due to Churchill & Chu, Raithby & Holland, Kuehn & Goldstein,Fand et al, Jaluria and Neeta et al are used to evaluate the free convectiveNusselt number as a function of Rayleigh number at orientations of 00, 100,200, 300, 400, 500, 600, 700, 800 and 900. Additionally, the Rayleigh numberis kept fixed at three regimes of 10-6, 100 and 106 and the free Nusseltnumber is evaluated as a function of the cylinder orientation. At maximumorientation (θ = 900) an increase of 114% in Nusselt number is observed forKuehn & Goldstein correlation